# Inelastic Collision - Kinetic Energy

JayaSuria
A 6.0kg metal ball moving at 4.0m/s hits a 6.0kg clay ball at rest and sticks to it. The two move at 2.0m/s.

a. calculate the kinetic energy of the metal ball before it hits the clay ball.
b. calculate the kinetic energy of the metal ball after it hits the clay ball.
c. calculate the kinetic energy of the clay ball after being hit.
d. calculate the energy that the metal ball lose in the collision.
e. calculate the kinetic energy that the clay ball gain in the collision.

I have answered (a), how to do (b) - (e)?? Plz help

Mentor
How did you solve (a)?

JayaSuria
@Doc Al == KE = 1/2mv^2.
(a) KE = 1/2 * 6 * 4^2 , equals to 48J

Mentor
@Doc Al == KE = 1/2mv^2.
(a) KE = 1/2 * 6 * 4^2 , equals to 48J
Good. Now use that same formula to do the rest.

JayaSuria
Good. Now use that same formula to do the rest.

@Doc Al , that's the hiccup. For inelastic collision, after the hit, how to calculate for separate objects as before collision? In that case, is the value in (b) same as (c)?

Mentor
@Doc Al , that's the hiccup. For inelastic collision, after the hit, how to calculate for separate objects as before collision? In that case, is the value in (b) same as (c)?
The mass of each is the same but the velocity changes. You are given the velocity before and after the collision, so just plug away into the formula to compute the KE of each before and after the collision. Then you can figure out how the energy changes.

JayaSuria
The mass of each is the same but the velocity changes. You are given the velocity before and after the collision, so just plug away into the formula to compute the KE of each before and after the collision. Then you can figure out how the energy changes.

@Doc Al owh thanks doc. Is this the solution?
(b) 1/2 * 6 * 2^2
(c) 1/2 * 6 * 2^2
(d) initial 48J, after 12J. Metal ball lost 36J
(e) initial 0J, after 12J. Clay ball gained 12J

Mentor
@Doc Al owh thanks doc. Is this the solution?
(b) 1/2 * 6 * 2^2
(c) 1/2 * 6 * 2^2
(d) initial 48J, after 12J. Metal ball lost 36J
(e) initial 0J, after 12J. Clay ball gained 12J
Looks good to me.

hanz and JayaSuria
hanz
Hi Doc, can u show me the calculation of kinetic energy loss by the metal ball?
Is there any calculation to this? instead by stating it only? for example KEloss=K1 - K2?
where k1 = intial KE of Metall Ball 48 J and K2 after collision 12 J, KEloss= 48-12 = 36 J
but if we do the same for clay ball where we calculate the KE gained by Clay ball using this formula
Kc1 = Kc1 intial KE which is Zero since the clay ball remain stationary, Kc2 = 12 J since it move together with the metal ball at 2.0 m/s
KEgain = Kc1 - Kc2
= 0 - 12 J
= - 12 J , As far as i know, Joule can never be negative, if we change the equation to Kc2-Kc1 we will get the right answer for the clay ball but for the metal ball it would become -36 J (which still negative numbers,except if I can explain that the negative symbol represent the loss of KE by metal ball, is it accepted that way? or KE can never be a negative numbers?)

hanz
Looks good to me.
Hi Doc, can u show me the calculation of kinetic energy loss by the metal ball?
Is there any calculation to this? instead by stating it only? for example KEloss=K1 - K2?
where k1 = intial KE of Metall Ball 48 J and K2 after collision 12 J, KEloss= 48-12 = 36 J
but if we do the same for clay ball where we calculate the KE gained by Clay ball using this formula
Kc1 = Kc1 intial KE which is Zero since the clay ball remain stationary, Kc2 = 12 J since it move together with the metal ball at 2.0 m/s
KEgain = Kc1 - Kc2
= 0 - 12 J
= - 12 J , As far as i know, Joule can never be negative, if we change the equation to Kc2-Kc1 we will get the right answer for the clay ball but for the metal ball it would become -36 J (which still negative numbers,except if I can explain that the negative symbol represent the loss of KE by metal ball, is it accepted that way? or KE can never be a negative numbers?)

hanz
I get it now, KEloss can be represent as KEloss=K1-K2 since we want to look for loss of energy therefore minus the intial, whereas KEgain = Ki + kf = 0 + 12
since we wanted to look for gain in kenetic energy therefore we add them together. Sorry pls ignore what i ask in the above

Mentor
I get it now, KEloss can be represent as KEloss=K1-K2 since we want to look for loss of energy therefore minus the intial, whereas KEgain = Ki + kf = 0 + 12
since we wanted to look for gain in kenetic energy therefore we add them together. Sorry pls ignore what i ask in the above
Surely, KE can never be negative. But the change in KE, which is always KEf - KEi, can be negative or positive depending on whether energy is lost or gained. (KEf + KEi has no meaning.)

hanz
hanz
Surely, KE can never be negative. But the change in KE, which is always KEf - KEi, can be negative or positive depending on whether energy is lost or gained. (KEf + KEi has no meaning.)
means it would be ok if metal ball KEloss=KEf-KEi= 12-48= -36 J? then just explain why it is negative?

Mentor
means it would be ok if metal ball KEloss=KEf-KEi= 12-48= -36 J?
The change in KE = - 36 J.

then just explain why it is negative?
A negative change means that the KE decreased. You can say that the metal ball lost 36 J of KE.

hanz